Analisis Tindak Tutur Direktif dalam Novel Antologi Rasa Karya Ika Natassa - Adela Agustiani; Irwan Siagian (Journal on Education, 2023)
The act of speech directive in Ika Natassa's novel "Antology Rasa" is discussed in this study. The goal of this research is twofold: (1) Describing the form of dialogue directives in Ika Natassa's novel Antology of Rasa; (2) Explaining the types of speech substances directives found in the novel Antology of Rasa. A pragmatic approach was used in this study. Pragmatics is a branch of psychology that studies the meaning of language. The researcher employs a descriptive qualitative method with note that read in this study. The data in this study are written data in the form of individual conversation data containing speech directives. Based on the results of the study, it can be determined that the form of the speech directive contained in the novel is a form of governing, asking, advocating, asking.